Using Social Media in pre-service teacher education: The case of a program-wide twitter hashtag. (April 2023) - Carpenter, Jeffrey P.; Morrison, Scott A.; Rosenberg, Joshua M.; Hawthorne, Katrice A.
Abstract: Herein we examine the use of a program-wide Twitter hashtag as a part of pre-service teacher education activities at one institution. After detailing the context around the hashtag's use, we use data mining, descriptive statistics, and social network analysis to examine more than 49, 000 tweets sent over six years. We describe the traffic associated with the program-wide Twitter hashtag, the users who contributed, and the interactions that occurred among pre-service teachers (PSTs) and other users. The hashtag appeared to feature some opportunities and challenges for PSTs to observe and interact with peers, alumni, faculty and staff, and in-service educators.